Did Dental Insurance Expansion Improve Dental Care Needs Among Korean Adults? Difference in Difference Analysis - Nam-Hee Kim; Hawazin W. Elani; Ichiro Kawachi (Journal of Epidemiology, 2023)
Background: In 2012, the Korean government expanded dental insurance for the elderly to promote improved access to dental care. We examined the causal effect of this policy on dental care needs, focusing on low-income older adults. Methods: We compared data before and after policy implementation using double difference (DD) and triple difference (DDD) analyses. We used the nationally representative data from the Korea National Health and Nutrition Examination Survey from 2010 and 2016–2018. Individuals aged ≥65 years were included in the treatment group, and individuals aged <65 years were included in the control group. Results: Dental insurance expansion was associated with a paradoxical increase in perceived unmet dental needs among elderly individuals (8.8 percentage points increase, 95% CI: 4.7 to 13.0). However, there were improvements in dental prosthetics outcomes (denture wearing [4.0 percentage points, 95% CI: 0.2 to 7.9] and dental implants [5.0 percentage points, 95% CI: 2.1 to 7.9]; P < 0.01). Upon analyzing low-income elderly individuals using DDD analysis, we found that the insurance expansion led to a 21.6% smaller increase in unmet dental needs among low-income adults, compared to high-income adults (95% CI, −35.0 to −8.5; P < 0.01). Conclusion: Dental insurance expansion in South Korea resulted in improvements in access to dental prosthetic services overall. It also led to a smaller increase in unmet dental needs among low-income older adults, compared to high-income adults.